Capacity Building Strategy in Samarinda Road Clinic: Strategi Penguatan Kapasitas (Capacity Building) di Klinik Jalanan Samarinda - Anwar, Syamsul; Fitriyarini, Inda (Progress In Social Development, 2020)
ABSTRACT: This study aims to identify and describe 3 (three) aspects of the capacity-building strategy of street children at the Samarinda Street Clinic, namely; Rehabilitation Aspects, Motivational Aspects, and Study Aspects. This study uses an observational approach. Before going down to the field, researchers did not bring or use any theory. The research location is in the Secretariat of the Street Clinic which is located at Jalan K.H. Agus Salim Gang 2, Kota Samarinda, and at the intersection of Jalan Basuki Rahmat traffic signs, Lembuswana Mall traffic sign intersection, Jalan Pangeran Antasari traffic sign intersection, and Sempaja traffic sign intersection. Sources of data come from primary data sources (key informants), namely Haerdy Pratama Wijaya, CEO of Samarinda Street Clinic, and secondary data from the literature. The data collection techniques used participant observation, in-depth interviews, and documentation. The results of this study indicate that 3 aspects of the capacity building strategy at the Samarinda Street Clinic are; aspects of rehabilitation, aspects of motivation, and aspects of studies that have been applied so far can rehabilitate some of the street children who have been addicted to gluing for a long time so that they don't cling anymore, and with the study aspect it can reduce the illiteracy rate of the street children being coached. ABSTRAK: Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan 3 (tiga) aspek strategi penguatan kapasitas (capacity building) anak jalanan di Klinik Jalanan Samarinda yaitu ; Aspek Rehabilitasi, Aspek Motivasi, dan Aspek Studi. Penelitian ini menggunakan pendekatan observasi. Sebelum turun kelapangan, peneliti tidak membawa atau menggunakan teori apapun. Lokasi penelitian di sekertariat Klinik Jalanan yang beralamat di Jalan K.H. Agus Salim Gang 2, Kota Samarinda dan di persimpangan rambu lalu lintas Jalan Basuki Rahmat, persimpangan rambu lalu lintas Mall Lembuswana, persimpangan rambu lalu lintas Jalan Pangeran Antasari dan persimpangan rambu lalu lintas Sempaja. Sumber data berasal dari sumber data primer (informan kunci) yaitu Haerdy Pratama Wijaya, CEO Klinik Jalanan Samarinda dan data sekunder yaitu dari kepustakaan. Teknik pengumpulan data menggungakan teknik participant observation, wawancara mendalam dan dokumentasi. Hasil penelitian ini menunjukkan bahwa 3 aspek strategi penguatan kapasitas (capacity building) di Klinik Jalanan Samarinda yaitu ; aspek rehabilitasi, aspek motivasi, dan aspek studi yang diterapkan selama ini mampu melakukan rehabilitasi kepada sebagian anak jalanan yang telah lama kecanduan ngelem sehingga tidak ngelem lagi, dan dengan adanya aspek studi dapat menekan angka buta huruf anak jalanan yang dibina.